Smoking and musculoskeletal disorders: findings from a British national survey. Issue 1 (1st January 2003) - Palmer, K T; Syddall, H; Cooper, C; Coggon, D
Abstract : Objectives: To explore the relation between smoking habits and regional pain in the general population. Methods: A questionnaire was mailed to 21 201 adults, aged 16–64 years, selected at random from the registers of 34 British general practices, and to 993 members of the armed services, randomly selected from pay records. Questions were asked about pain in the low back, neck, and upper and lower limbs during the past 12 months; smoking habits; physical activities at work; headaches; and tiredness or stress. Associations were examined by logistic regression and expressed as prevalence ratios (PRs). Results: Questionnaires were completed by 12 907 (58%) subjects, including 6513 who had smoked at some time, among whom 3184 were current smokers. Smoking habits were related to age, social class, report of headaches, tiredness or stress, and manual activities at work. After adjustment for potential confounders, current and ex-smokers had higher risks than lifetime non-smokers for pain at all of the sites considered. This was especially so for pain reported as preventing normal activities (with PRs up to 1.6 in current v never smokers). Similar associations were found in both sexes, and when analysis was restricted to non-manual workers. Conclusions: There is an association between smoking and report of regional pain, which is apparent even in ex-smokers. This could arise from a pharmacological effect of tobacco smoke (for example, on neurological processing of sensory information or nutrition of peripheral tissues); another possibility is that people with a low threshold for reporting pain and disability are more likely to take up and continue smoking.